2005
DOI: 10.1097/01.prs.0000160695.33457.db
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Breast Reduction Complications Derived from the BRAVO Study

Abstract: Complication data revealed several significant features: (1) resection weight correlated with increased risk and absolute number of complications; (2) delayed healing correlated directly with resection weight and inversely with increasing age, anesthesia times, and preoperative Short Form-36 bodily pain score; (3) a vertical incision may be associated with increased incidence of complications but requires further analysis; and most importantly, (4) the presence of complications had no negative effect on improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
124
5
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(153 citation statements)
references
References 0 publications
18
124
5
6
Order By: Relevance
“…[16] Other studies similarly found no statistically significant difference in complication rates among the obese. [14,15,17] However, contradictory findings exist in the literature as well, supporting obesity as a risk factor. [6,[9][10][11][12][13] Chun et al [13] identified a threshold of BMI 35.6 at which postoperative complications were increased two-fold, the most common complication being infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[16] Other studies similarly found no statistically significant difference in complication rates among the obese. [14,15,17] However, contradictory findings exist in the literature as well, supporting obesity as a risk factor. [6,[9][10][11][12][13] Chun et al [13] identified a threshold of BMI 35.6 at which postoperative complications were increased two-fold, the most common complication being infection.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies associate obesity with increased postoperative complications, [9][10][11][12][13] whereas others find no statistically significant correlation. [14][15][16][17] In 2014, Nelson et al [6] studied obesity and reduction mammaplasty using the 2005-2011 American College of Surgeons -National Surgical Quality Improvement Program (ACS-NSQIP) datasets. NSQIP is a nationally-validated, risk-adjusted surgical outcomes database to measure and improve the quality of surgical care.…”
Section: Introductionmentioning
confidence: 99%
“…По данным литературы, частота гематом при редук-ционной пластике составляет 0,3-5% [1,2], по нашим данным -2,9%.…”
Section: таблица 1 корригирующие операции на здоровой и сформированнunclassified
“…Подобное осложнение при редукционной маммопла-стике с перемещением САК на вертикальной деэпители-зированной ножке по Lejour, по данным литературы, со-ставляет 1-35% [1,2], у нас -2,9%.…”
Section: таблица 1 корригирующие операции на здоровой и сформированнunclassified
“…The reduction mammoplasty operation is one of the procedures frequently performed in plastic surgery [1,2]. There are many techniques described in relation to reduction mammoplasty surgery; however, the common characteristic of these techniques are considerable blood loss during and after the operation [3].…”
Section: Introductionmentioning
confidence: 99%